The Metallicity and Carbon-to-oxygen Ratio of the Ultrahot Jupiter WASP-76b from Gemini-S/IGRINS - Weiner Mansfield, M; Line, MR; Wardenier, JP; Brogi, M; Bean, JL; Beltz, H; Smith, P; Zalesky, JA; Batalha, N; Kempton, EM; Montet, BT; Owen, JE; et al. (IOP Publishing, 2024)
Measurements of the carbon-to-oxygen (C/O) ratios of exoplanet atmospheres can reveal details about their formation and evolution. Recently, high-resolution cross-correlation analysis has emerged as a method of precisely constraining the C/O ratios of hot Jupiter atmospheres. We present two transits of the ultrahot Jupiter WASP-76b observed between 1.4 and 2.4 μm with the high-resolution Immersion GRating INfrared Spectrometer on the Gemini-S telescope. We detected the presence of H2O, CO, and OH at signal-to-noise ratios of 6.93, 6.47, and 3.90, respectively. We performed two retrievals on this data set. A free retrieval for abundances of these three species retrieved a volatile metallicity of C+OH=−0.70−0.93+1.27 , consistent with the stellar value, and a supersolar carbon-to-oxygen ratio of C/O =0.80−0.11+0.07 . We also ran a chemically self-consistent grid retrieval, which agreed with the free retrieval within 1σ but favored a slightly more substellar metallicity and solar C/O ratio ( C+OH=−0.74−0.17+0.23 and C/O =0.59−0.14+0.13 ). A variety of formation pathways may explain the composition of WASP-76b. Additionally, we found systemic (V sys) and Keplerian (K p ) velocity offsets which were broadly consistent with expectations from 3D general circulation models of WASP-76b, with the exception of a redshifted V sys for H2O. Future observations to measure the phase-dependent velocity offsets and limb differences at high resolution on WASP-76b will be necessary to understand the H2O velocity shift. Finally, we find that the population of exoplanets with precisely constrained C/O ratios generally trends toward super-solar C/O ratios. More results from high-resolution observations or JWST will serve to further elucidate any population-level trends.